Students’ Perception through TIKTOK Video in Writing Procedure Text at Second Grade of SMKN 6 Padang - Mitra Reflia; Yessy Marzona; Widya Juli Astria (JURNAL ARMADA PENDIDIKAN, 2026)
The purpose of this research was to identify the students’ perception through TikTok video in writing procedure text at second grade of SMKN 6 Padang. The students have three problems, some students were lazy to learn English, monotonous learning supported by books, many students lack of interested in writing procedure text. The sample of the data in this study was students of class culinary department at second grade of SMKN 6 Padang. The method in this study was descriptive qualitative research. The population was 32 students and the sample consists of total sample students. The data were obtained from the questionnaire, The researcher gave 20 items of statement which was from three indicators (title, material, step). Researcher used likert scale to data analysis. Based on the results of the questionnaire given, the researchers found that the students’ perception through TikTok video in writing procedure text at second grade of SMKN 6 Padang are in the strongly category with a percentage of 65.5%. It was indicated by the scientific fact that, in terms of titles 76.58% In terms of material, 75.84% students have a positive perception. Addition, 78.55% students had a positive perception of the step. The researcher concluded that students’ perception through TikTok video in writing procedure text was positive.